Penerapan Model Pembelajaran TGT dengan Alat Peraga Ultaphygo untuk Meningkatkan Hasil Belajar Matematika Siswa - Hari Aningrawati Bahri; Herlina Rifai (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2020)
This research is a classroom action research with the aim of knowing the improvement of student mathematics learning outcomes throught the application of the TGT learning model with Ultaphygo teaching aids. This research includes planning, implementing, observing, and reflecting. motivated by the low learning outcomes of students at SMK Mega Link Majene in mathematics. The research subjects were students of class X SMK Mega Link Majene. Data collection techniques used student activity observation sheets, learning implementation observation sheets, and student learning outcomes tests at the end of each cycle. Each data collected at the end of the cycle was analyzed quantitatively by using descriptive statistics for student learning outcomes, while student activity and learning implementation used qualitative analysis. The results showed an increase in student learning outcomes from pre cycle to first cycle. This can be seen in the average student learning outcomes in the pre-cycle test results of 78.34, then an increase in the first cycle with an  average student learning outcomes of 87.66 with a completeness percentage of 89.05% of 37 students. Likewise, student activity also experienced an increase from pre-cycle an average of 78% to an average of 93% in the first cycle with the very good category. Based on the description, it can be concluded that there is an increase in the learning achievement of students' mathematics learning activities through the application of the TGT learning model using Ultaphygo teaching aids.